Admission troponin-I predicts subsequent cardiac complications and mortality in acute stroke patients. (September 2016) - Bustamante, Alejandro; Díaz-Fernández, Belén; Pagola, Jorge; Blanco-Grau, Albert; Rubiera, Marta; Penalba, Anna; García-Berrocoso, Teresa; Montaner, Joan
Purpose: The importance of troponin elevation at stroke presentation remains uncertain. We aimed to assess whether baseline ultrasensitive Troponin I (hs-TnI) predicts cardiac complications and outcome in acute stroke patients. Method: Stroke patients admitted within 6 h were consecutively enrolled from May 2013 to March 2014. Blood samples were taken at admission to determine hs-TnI by chemiluminescent microparticle immunoassay. hs-TnI > 34.2 pg/ml (male) and >15.6 pg/ml (female) were considered elevated. Complications during in-hospital stay and outcome at 90 days were prospectively recorded. Independent predictors of cardiac complications (heart failure and acute coronary syndrome) and mortality were determined by logistic regression. The additional predictive value of hs-TnI was evaluated by integrated discrimination improvement index. A subanalysis was performed after excluding patients with previous cardiac diseases. Findings: From 174 patients, 39(22%) had elevated hs-TnI, having these patients higher incidence of cardiac complications (57% versus 19%, p = 0.004). hs-TnI was an independent predictor of cardiac complications (OR = 16.1 (1.7–150.3)) together with diastolic blood pressure (OR = 0.92 (0.86–0.99)). Addition of hs-TnI to clinical variables significantly improved discrimination (IDI = 15.2% (7.8–22.7)). Subanalysis in patients without previous cardiac diseases showed similar results. Elevated hs-TnI was independently associated with 90 days mortality (OR = 3.6 (1.3–9.4)), but addition of hs-TnI to clinical data did not result in an increased discrimination. Discussion: The present study confers hs-TnI a 2b level of evidence as a diagnostic tool to predict cardiac complications in stroke. Absence of serial hs-TnI measurements and limited sample size are the main weaknesses of the study. Conclusion: Patients with elevated baseline hs-TnI showed a higher frequency of cardiac complications and a higher mortality. Measurement of hs-TnI in acute stroke might be useful to identify patients at a high risk of cardiac complications and death.